Pemanfaatan digitalisasi untuk meningkatkan usaha koperasi - febriany, felia (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has brought significant changes in various aspects of life, including the cooperative sector. Digitalization creates new opportunities for cooperatives to increase competitiveness, expand markets, and strengthen organizational governance. This study aims to examine the utilization of digitalization as a strategy to improve cooperative businesses, both in terms of operations and member services. The method used is a literature study through analysis of relevant references and sources related to the implementation of digital technology in cooperatives. The results show that the adoption of digital accounting systems, online marketing applications, and the use of social media can help cooperatives expand their business networks, improve transparency, and facilitate easier service access for members. In addition, digitalization contributes to administrative efficiency, data accuracy, and faster information-based decision-making. However, the main challenges faced are limited digital literacy, technology investment costs, and human resource readiness. With the right strategy, digitalization has great potential to drive the growth of cooperatives, enabling them to compete in the digital economy era and provide optimal benefits for their members.